2019
DOI: 10.1002/prp2.460
|View full text |Cite
|
Sign up to set email alerts
|

Combined antitumoral effects of pretubulysin and methotrexate

Abstract: Pretubulysin (PT), a potent tubulin‐binding antitumoral drug, and the well‐established antimetabolite methotrexate (MTX) were tested separately or in combination (PT+MTX) for antitumoral activity in L1210 leukemia cells or KB cervix carcinoma cells in vitro and in vivo in NMRI‐nu/nu tumor mouse models. In cultured L1210 cells, treatment with PT or MTX displays strong antitumoral effects in vitro, and the combination PT+MTX exceeds the effect of single drugs. PT also potently kills the MTX resistant KB cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 49 publications
0
15
1
Order By: Relevance
“…Additionally, we observed CCRF-CEM cell accumulation in both S-and G 2 /M phases of the cell cycle after the combined treatment, which seems to have been an additive effect, since methotrexate and CX-4945 used individually led to G 2 /M- phase arrest and S-phase arrest, respectively. Interestingly, our results demonstrating G 2 /M-phase arrest after methotrexate treatment are contrary to previous results obtained for L1210 mouse leukemia suggesting that methotrexate cytotoxicity is related to irreversible S-phase and G 1 /S-phase arrest (9,24). S-Phase arrest occurring after CK2 inhibition in the CCRF-CEM line is consistent with our previous data demonstrating the effect of another CK2 inhibitor, 4,5,6,7-tetrabromo-2-methyl-1H-benzimidazol-1-yl)acetonitrile, on cell-cycle progression in this cell line (17).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Additionally, we observed CCRF-CEM cell accumulation in both S-and G 2 /M phases of the cell cycle after the combined treatment, which seems to have been an additive effect, since methotrexate and CX-4945 used individually led to G 2 /M- phase arrest and S-phase arrest, respectively. Interestingly, our results demonstrating G 2 /M-phase arrest after methotrexate treatment are contrary to previous results obtained for L1210 mouse leukemia suggesting that methotrexate cytotoxicity is related to irreversible S-phase and G 1 /S-phase arrest (9,24). S-Phase arrest occurring after CK2 inhibition in the CCRF-CEM line is consistent with our previous data demonstrating the effect of another CK2 inhibitor, 4,5,6,7-tetrabromo-2-methyl-1H-benzimidazol-1-yl)acetonitrile, on cell-cycle progression in this cell line (17).…”
Section: Discussioncontrasting
confidence: 99%
“…Other studies have shown that the combination of methotrexate and suberoylanilide hydroxamic acid (a histone deacetylase inhibitor) has a synergistic effect in leukemia cells with combination index values in the range of 0.64-0.84, depending on the cell line used (for CCRF-CEM with line: CI=0.84) (8). The most recent research carried out on L1210 mouse lymphocytic leukemia cell line showed that combined treatment of pretubulysin, a potent tubulin-binding antitumoral drug, with methotrexate displayed strong anticancer effects in both in vitro and in vivo models (9). DHFR, with two other enzymes, namely thymidylate synthase (TYMS), and serine hydroxymethyltransferase (SHMT), constitute the thymidylate synthesis cycle, providing the substrate required for DNA synthesis and repair (10).…”
mentioning
confidence: 99%
“…The IC 50 value of the formulation was significantly lower than those of free drugs. The use of MTX and a potent tubulin-binding anti-tumoural drug pretubulysin, alone and in the form of a combined regimen, is described by Kern et al [224] The authors demonstrated the benefits of using the drug regimen and indicated that it was a promising therapeutic approach for various types of cancer, among other in lung cancer therapy. Sekimura et al presented a case of primary lung cancer with MTX-associated lymphoproliferative disorder [271] which occurred in a patient receiving oral MTX and prednisolone for RA for about 15 years.…”
Section: Methotrexate-based Therapy Of Lung Cancermentioning
confidence: 99%
“…Apoptosis is a severe toxic phenomenon marked by cell shrinkage, chromatin condensation, nuclear DNA fragmentation, a decrease in the mitochondrial membrane potential (MMP) and caspase activation . MTX exerts its antitumour effects via the induction of apoptosis in many cancers . Unfortunately, it can also induce apoptosis in healthy tissues, including the testes, and the underlying molecular mechanism is poorly characterized.…”
Section: Introductionmentioning
confidence: 99%
“…9 MTX exerts its antitumour effects via the induction of apoptosis in many cancers. [10][11][12] Unfortunately, it can also induce apoptosis in healthy tissues, including the testes, 13,14 and the underlying molecular mechanism is poorly characterized. Autophagy is an intracellular system that degrades damaged cytoplasmic components and proteins to eliminate old and unhealthy cells.…”
mentioning
confidence: 99%